2017
DOI: 10.1038/s41598-017-18085-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional and cooperative stabilization of a two-metal (Ca, Zn) center in α-amylase derived from Flavobacteriaceae species

Abstract: Mesophilic α-amylase from Flavobacteriaceae (FSA) is evolutionary closely related to thermophilic archaeal Pyrococcus furiosus α-amylase (PWA), but lacks the high thermostability, despite the conservation of most residues involved in the two-metal (Ca, Zn) binding center of PWA. In this study, a disulfide bond was introduced near the two-metal binding center of FSA (designated mutant EH-CC) and this modification resulted in a slight improvement in thermostability. As expected, E204G mutations in FSA and EH-CC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…SPR results (Figure 3b-d Fallal, 2017;Kuddus, 2017;Yin et al, 2017). Lower concentration salt may improve the stability of α-amylase activity.…”
Section: Effect Of Ph and Salt On The Interaction Between Three Flavo...mentioning
confidence: 95%
See 1 more Smart Citation
“…SPR results (Figure 3b-d Fallal, 2017;Kuddus, 2017;Yin et al, 2017). Lower concentration salt may improve the stability of α-amylase activity.…”
Section: Effect Of Ph and Salt On The Interaction Between Three Flavo...mentioning
confidence: 95%
“…I G U R E 3 SPR response for the interaction of three flavonoids (200 μM) and α-amylase (300 μM) with various pH values (a), various concentrations of KCl (b), various concentrations of MgCl 2 (c), and various concentrations of CaCl 2 (d) at room temperature is 0.150 M. Similar results are also observed from Figure 3d, the optimal CaCl 2 concentration is 0.100 M for the binding of acacetin, buddleoside with α-amylase. On the other hand, many studies have confirmed that some metal ions (K + , Mg 2+ , and Ca 2+ ) can maintain the maximum reactivity of the enzyme (El-Sayed,Abou-Dobara, & El- Fallal, 2017;Kuddus, 2017;Yin et al, 2017). On the one hand, α-amylase is a metalloenzyme (Gupta, Gigras, Mohapatra, Goswami, & Chauhan, 2003),and Cl − is activator of the α-amylase(Kuriki & Imanaka, 1999).…”
mentioning
confidence: 99%
“…In spite of the increased activity (3.2%) detected by introducing a new disulphide linkage in FSA at E200C and H201C, enhanced ligand-dependent thermostability i.e., Ca 2+ and Zn 2+ was detected after the incubation at 50C for 30 min when E204G and C214S mutations were performed ( Yin et al, 2017 ). Nonetheless, the improvement in thermostability ( t 12 at 95C) at 26-fold (Ca 2+ -absent) and 5-fold (Ca 2+ -present) was observed when the loop deletion of I181 and G182 (IG) coupled with N193F and S242A were performed on the maltohexaose-forming -amylase from B. stearothermophilus (AmyMH) ( Li, Duan & Wu, 2016 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…These metals could be bridged by a residue which is specific to the enzyme [15]. Yin and coauthors [31] [32]. Babu & Satyanarayana [33] also reported that while calcium inhibited the activity of the α-amylase from Bacillus coagulans B49, Mn 2+ slightly stimulated the amylase activity.…”
Section: Reactivation Of Rsda With Different Metal Cationsmentioning
confidence: 99%